Pertumbuhan tanaman bayam horenzo (Spinacia orelacea L.) dengan pemberian nutrisi menggunakan ekoenzim - Nurfadilah, Febby; Surtikanti, Hertien Koosbandiah; Nilawati, Tina Safaria (Holistic: Journal of Tropical Agriculture Sciences, 2024)
Horenzo spinach (Spinacia oleracea L.) is one of the vegetable commodities that is currently in great demand by the public, however the cultivation process is still very limited so it requires optimal cultivation methods. Ecoenzyme is an organic solution that can be used in horenzo spinach cultivation as a substitute for fertilizer, because it contains nutrients that plants need. The ecoenzymes used are sourced from vegetable waste (mustard greens and lemongrass) and fruit peels (pineapple, mango, banana, watermelon and orange). This research was conducted to examine the potential of ecoenzymes and obtain optimal concentrations of ecoenzyme administration for the growth of Horenzo spinach plants. There were 6 treatments in this study, namely without treatment as a negative control (E0), giving a mixture of white CNG and KNO3 fertilizer as a positive control (E1) and giving different doses of ecoenzymes, namely 1ml/l (E2), 5ml/l (E3), 10 /l (E4) and 15ml/l (E5). Observations were carried out for 42 days with the parameters observed, namely vegetative growth (plant height, leaf length, leaf width, number of leaves, root length, root volume and plant organ biomass) as well as the chlorophyll content of the leaves of the Horenzo spinach plant. The data that had been obtained was then analyzed by Post-Hoc Tukey test data which showed that treatment E1 had significantly different results from other treatments and treatment E5 was an ecoenzyme treatment that had the potential to increase the growth of horenzo spinach plants. The conclusion obtained from this research is that the highest dose of ecoenzyme is not optimal in increasing the growth of Horenzo spinach plants from all test parameters, however E5 treatment has the potential to increase the growth of Horenzo spinach.